Implementasi Guided Imagery & Slow Deep Breathing untuk Menurunkan Tekanan Darah Pada Ibu Hamil di Desa Bangun Rejo Tahun 2025 - Lisdayanti Simanjuntak; Dina Afriani; Eko Murdianto; Sri Mulati Nendah Agreta; Reja Gusmela Lumbantoruan (Jurnal Kemitraan Masyarakat, 2025)
Background: Depression is the most common psychological disorder that occurs in the last years of an individual's life. Elderly depression has several impacts, including shortening life expectancy by worsening physical decline in the elderly, inhibiting the fulfillment of elderly developmental tasks, reducing the quality of life of the elderly, draining the emotions and finances of the affected person and their family and social support system. The physiotherapy program given to the elderly who experience depression includes listening to classical English music and murottal. Purpose: For this reason, this community service activity aims to socialize the provision of classical English music therapy and murottal to reduce the level of depression in the elderly. : This community service activity uses the lecture practice and question and answer method. The lecture method is carried out by delivering material about depression and English music therapy. After that, practice listening to classical English music and Murottal, while the question and answer method is carried out by asking participants about the material that has been presented. Results: The results of this community service activity showed that participants were able to understand and apply the material that had been presented. Conclusion: Based on the community service activities that have been carried out, many of the participants were enthusiastic about receiving the entire series of events starting from the presentation of the material, practicing listening to classical English music to question and answer interactions.